The impact of brain‐derived neurotrophic factor Val66Met polymorphism on cognition and functional brain networks in patients with intractable partial epilepsy. (27th June 2018) - Sidhu, Meneka K.; Thompson, Pamela J.; Wandschneider, Britta; Foulkes, Alexandra; de Tisi, Jane; Stretton, Jason; Perona, Marina; Thom, Maria; Bonelli, Silvia B.; Burdett, Jane; Williams, Elaine; Duncan, John S.; et al.
Summary: Introduction: Medial temporal lobe epilepsy (mTLE) is the most common refractory focal epilepsy in adults. Around 30%‐40% of patients have prominent memory impairment and experience significant postoperative memory and language decline after surgical treatment. BDNF Val66Met polymorphism has also been associated with cognition and variability in structural and functional hippocampal indices in healthy controls and some patient groups. Aims: We examined whether BDNF Val66Met variation was associated with cognitive impairment in mTLE. Methods: In this study, we investigated the association of Val66Met polymorphism with cognitive performance (n = 276), postoperative cognitive change (n = 126) and fMRI activation patterns during memory encoding and language paradigms in 2 groups of patients with mTLE (n = 37 and 34). Results: mTLE patients carrying the Met allele performed more poorly on memory tasks and showed reduced medial temporal lobe activation and reduced task‐related deactivations within the default mode networks in both the fMRI memory and language tasks than Val/Val patients. Conclusions: Although cognitive impairment in epilepsy is the result of a complex interaction of factors, our results suggest a role of genetic factors on cognitive impairment in mTLE.